Stepping to the dance - Carolyn Cressy Wells (Brooks/Cole Pub. Co., 1998)
This book shows the interweaving of issues occurring in the lives of the therapist and the clients served. The reader is introduced to JoEllen Madsen, a family counselor who is facing her own personal challenges, and the Petersons, a family that includes parents struggling with marital difficulties and a son and daughter who are having serious problems in school. The Petersons enter into family therapy with JoEllen, now a student in a post-graduate training program. As readers follow the course of therapy, they will be engaged both emotionally and intellectually. Provocative reading, the book illustrates the complexity of family therapy, the skills and techniques involved, and the importance of ongoing consultation, supervision, and personal work by the therapist